Prospective evaluation of the clinical utility of single-operator peroral cholangioscopy in patients with primary sclerosing cholangitis - Arnelo, Urban; von Seth, Erik; Bergquist, Annika (Endoscopy, 2015)
Background and study aims: The role of cholangioscopy in primary sclerosing cholangitis (PSC) using a single-operator peroral cholangioscopy direct visualization system is unknown. This study aimed to prospectively evaluate the clinical utility of the system in PSC patients undergoing endoscopic retrograde cholangiopancreatography (ERCP). Patients and methods: Patients with PSC or suspicion of PSC and a clinical indication for ERCP were enrolled between September 2008 and May 2011. Patients underwent cholangioscopy with sampling from biliary strictures. Clinical data, technical information from the ERCP procedure, and results from sampling by brush cytology and mini-forceps biopsy were collected. Long-term follow-up was conducted. Outcomes included technical success, sampling adequacy, and diagnostic accuracy of cholangioscopy-guided sampling for detection of cholangiocarcinoma (CCA). Results: A total of 47 patients with PSC were included in the study. Median follow-up time was 27 months (range 2 – 64 months). Technical success was achieved in 96 % (45/47). In 9 % (4/45), the target lesion could not have been reached without the cholangioscopic visualization of the bile duct, which enabled further advancement of the investigation. A total of 64 biliary strictures were evaluated. Sample quality was adequate in 98 % (62/63) of the cytology brushings and in 95 % (21/22) of the mini-forceps biopsies. Of the three patients with a final diagnosis of CCA, one was diagnosed at the time of the investigation. The sensitivity, specificity, accuracy, and negative predictive value were 33 %, 100 %, 96 %, and 95 %, respectively.Conclusion: Cholangioscopy and cholangioscopy-guided sampling can be utilized successfully in patients with PSC. Cholangioscopy enabled targeted biopsies to be taken and was able to pass otherwise inaccessible strictures, making it potentially valuable for the management of biliary strictures in patients with PSC.Trial registered at ClinicalTrials.gov (NCT01556555).